Acute potentiating effect of depth jumps on sprint performance - Byrne, P. J.; Kenny, J.; O` Rourke, B. (The Journal of Strength and Conditioning Research, 2014)
The purpose of this investigation was to determine whether the addition of 3 depth jumps to a dynamic warm-up (DYNDJ) protocol would significantly improve 20-m sprint performance when compared with a cardiovascular (C) warm-up protocol or a dynamic (DYN) stretching protocol alone. The first part of the study identified optimal drop height for all subjects using the maximum jump height method. The identified optimal drop heights were later used during the DYNDJ protocol. The second part compared the 3 warm-up protocols above to determine their effect on 20-m sprint performance. Twenty-nine subjects (age, 20.8 ± 4.4 years; weight, 82.6 ± 9.9 kg; height, 180.3 ± 6.2 cm) performed 3 protocols of a C protocol, a DYN protocol, and a DYNDJ protocol in a randomized order. A 20-m sprint was performed 1 minute after the completion of each of the 3 protocols. Results displayed significant differences between each of the 3 protocols. A significant improvement (p = 0.001) of 2.2% was obtained in sprint time between the C protocol (3.300 ± 0.105 seconds) and the DYN protocol (3.227 ± 0.116 seconds), a further significant improvement of 5.01% was attained between the C and the DYNDJ protocols (3.300 ± 0.10 vs. 3.132 ± 0.120 seconds; p = 0.001). In addition, a significant improvement (p = 0.001) of 2.93% was observed between the DYN protocol (3.227 ± 0.116 seconds) and the DYNDJ protocol (3.132 ± 0.116 seconds). The data from this study advocate the use of DYNDJ protocol as a means of significantly improving 20-m sprint performance 1 minute after the DYNDJ protocol.